SURVEI KEPADATAN LALAT DI TEMPAT PEMBUANGAN AKHIR (TPA) SAMPAH JATIBARANG TAHUN 2017 - Masyhuda Masyhuda; Retno Hestiningsih; Rully Rahadian (Jurnal Kesehatan Masyarakat (Undip), 2017)
The garbage problems are negative effects of the growing population, the impact of garbage indirectly as the breeding place of vector born disease that is flies. Flies have significant roles for several public health problems.Data on density and type of flies needed to knowwhere and how the population control of flies could applied effectively and efficiently.This research conducted in Jatibarang landfill. The general objective of this research is to know the density flies in Jatibarang landfill Semarang. This research is an exploratory research with cross sectional approach. The population in this research is all the flies in Jatibarang landfill Semarang. The sampling applied in this research is an accidental sampling techniques. The observation was conducted in 3 different areas in 3 different times. The number of flies active zone I 1.707 individual, active zone II 793 individual and passive zone 225 individual.This research showedmore than half of the total flies that caught found in the area active zone I (63%). This research recomendedmanagement of landfill Jatibarang to prefer control of flies population in active zone I and people living in residential area around landfill Jatibarang have to close and protecttableware, food and man from contact directly with flies.